The Fourth Plenum of the CPC Makes an Important Decision on Law Reform in China - Kjeld Erik Brødsgaard; Nis Grünberg (The Copenhagen Journal of Asian Studies, 2015)
During the Fourth Plenary Session of the 13th Communist Party of China (CPC) Congress, a new and important reform document was adopted. Announcing reforms mainly in the juridical sector, the 'Decision of the CPC Central Committee Concerning Some Major Questions in Comprehensively Moving Governing the Country According to the Law Forward' is part of the overall reform package kicked off at the Third Plenum last year. This article points out the document's main objectives, and provides a preliminary analysis of the announced reforms. Three main themes are identified. First, the document is part of the overall goal of developing a special Chinese system of 'socialism with Chinese characteristics'. Second, not only institutions but also the minds and work styles of officials are to be reformed. Third, the document strongly affirms the CPC's role as the legal guardian of the reform process, as well as juridical matters.